Association of osteoporosis with genetic variants of circadian genes in Chinese geriatrics. Issue 4 (April 2016) - Li, Y.; Zhou, J.; Wu, Y.; Lu, T.; Yuan, M.; Cui, Y.; Zhou, Y.; Yang, G.; Hong, Y.
Abstract Summary This study was designed to investigate the association of circadian gene single nucleotide polymorphisms (SNPs) with the risk of osteoporosis. We found that the rs3781638 GG genotype was positively associated with osteoporosis prevalence in females, whereas the rs2292910 AC genotype was negatively associated with osteoporosis prevalence in a geriatric cohort. Introduction Studies have shown that disruption of endogenous circadian rhythms may increase the risk of developing type II diabetes and obesity, which are reportedly associated with osteoporosis (OP). Thus, abnormalities of circadian genes may indirectly induce OP. Here, we investigated the association of OP with 14 SNPs located in seven circadian genes. Methods The research subjects, geriatric residents of Shanghai Minhang, China, diagnosed with OP (N  = 171) or osteopenia (N  = 226) or without specific diseases (N  = 200), were genotyped for 14 genetic variants of circadian genes by competitive allele-specific polymerase chain reaction. The prevalence of polymorphisms among the subject groups and the association between the SNPs and osteoporosis were investigated. Results Among the 14 genotyped SNPs, we found an association between the CRY2 gene rs2292910 SNP and osteoporosis (r  = −0.082, p  = 0.045) in the geriatric cohort. We found a decreased risk between cryptochrome 2 rs2292910 and OP (A/C odds ratio = 0.647, p  = 0.044) but an increased risk between MTNR1B rs3781638 and OP (G/G odds ratio = 2.058, p  = 0.044). Conclusion For the first time, we show that Cry 2 rs2292910 and MTNR1B rs3781638 are associated with osteoporosis in a Chinese geriatric cohort. Therefore, targeting the abnormalities of the CRY2 and MTNR1B genes may be a potential strategy to treat and/or to prevent osteoporosis.